A numerical study of the effects of shot peening on the short crack growth behaviour in notched geometries under bending fatigue tests. (October 2017) - You, C.; Achintha, M.; He, B.Y.; Reed, P.A.S.
Graphical abstract: Highlights: An FE model is used to study the short crack growth behaviour in shot-peened samples. The retardation of short crack growth resulting from shot peening is quantified. Compressive residual stresses can effectively mitigate short crack propagation. Strain hardening can hinder crack initiation but may accelerate crack propagation. LEFM and EPFM are compared to highlight their advantages and drawbacks. Abstract: The current paper presents a numerical analysis of the effects of shot peening on short crack growth in a low pressure (LP) steam turbine material, FV448. The fatigue behaviour of this material has been experimentally evaluated using a U-notched specimen (representing the fir tree root geometry of the turbine blade) under 3-point bend tests. Two different shot peening intensities were considered in this study: an industrially applied shot peening process and a less intense shot peening process. In the modelling work, a 2-D finite element (FE) model with static short cracks has been developed, incorporating both compressive residual stress and strain hardening distribution effects caused by shot peening. Both linear-elastic (LEFM) and elasto-plastic (EPFM) fracture mechanics were used to characterise the crack driving force in the un-peened and shot-peened conditions, taking into account the effects of stress redistribution caused by residual stress relaxation and crack opening. The stress intensity factor used in the LEFM approach was calculated using the weight function method, and the equivalent stress intensity factor used in the EPFM approach was calculated from the J-integral, which was evaluated using the cracked FE model. These results could explain the mechanism of (experimentally observed) retardation of crack growth through the shot-peening-affected layer and also quantified this influence on fatigue life. The relative contributions of compressive residual stresses and strain hardening were assessed by investigating them separately. The sub-surface compressive residual stress distribution produced by shot peening could effectively reduce crack propagation but the strain hardening distribution, in contrast, can accelerate it. However, strain hardening is expected to hinder the crack initiation process by restricting the plastic deformation during cyclic loading. Predictions of the fatigue life of the shot-peened notched specimens were made based on this numerical analysis. Acceptable results were obtained using both the LEFM and EPFM approaches and the difference between them is discussed.